Study on Dynamic Response Laws and Shock Absorption Measures of Mountain Tunnel under Strong Earthquake - Zhi Lin; Lei Yan; Chen Xiang; Hongyun Yang (Advances in Civil Engineering)
Based on the longitudinal and transverse seismic and shock absorption theory of tunnel structure, relying on the actual engineering, a finite element analysis model of a typical mountain tunnel was established. Four calculation conditions including the presence or absence of shock absorption layers and seismic joints are defined. The principal tensile (compressive) stress and displacement response of the vault, arch waist, foot of side wall, and middle of invert are studied. The results show that the shock absorption layer and the seismic joint have great influence on the dynamic response of the tunnel structure, which can reduce the main tensile (pressure) stress of different parts of the lining and change the way of stress distribution. The peak principal tensile (pressure) stress of the lining is reduced more obviously when the shock absorption layer and seismic joint are set. However, the presence of the shock absorption layer and the seismic joint will increase the peak displacement of each monitoring point of lining. The displacement of each monitoring point of lining is increased more obviously by the single shock absorption layer. Therefore, when the seismic design of the tunnel structure is carried out, the maximum seismic demand of the tunnel structure should be determined according to the specific calculation content in order to guide the design.